Comunicação, relações e culturas : as assessorias de imprensa no tecer complexo das organizações públicas - Strelow, Patrícia Hammes (2015)
The Information Age has modified the way the man creates relationships and has deeply impacted the organizations in the 21st Century. We live in a world connected by digital technology networks in which subjective values are superimposed to material assets a scenario that demands a complex look to be understood. In this study we present an analysis of the production process of Communication inside the public organizations, starting from a theoretical background supported by authors who understand the Organization as a product of the relationships between the subjects, namely, as a fundamentally culture reality construed through the interactions made possible by Communication. Through the lenses of the Complexity Paradigm, by Edgar Morin, we analyze how Culture is influenced and also influences the construction of policies of Organizational Communication set forth by Press Officers, the way in which the practices of the press officers are aligned with the contemporary concept of Integrated Strategic Planning, and how the human dimension of the Organization is inserted into the process for the construction of said policies. This study focus on the Press Officer but expands over the Communication Office and its relationship with the Organization, since it is understood that the parts are intrinsic to the whole. A field research is performed through in-depth interviews with professionals in the Communication area into autarchies in the Government of Rio Grande do Sul. The Analysis of Content, by Laurence Bardin, is the technique through which we seek to understand and explain the process of production of communication policies by the press officers.